Kinerja Membran Mikrofiltrasi Untuk Menjadikan Air Olahan Instalasi Pengolahan Air Limbah Rumah Sakit Menjadi Air Bersih - Santosa, Imam; Br Ginting, Daria; Murwanto, Bambang; Telaumbanua, Mareli (Poltekkes Kemenkes Tanjung Karang, 2024)
Problems arise when there are tax fees on groundwater use by hospitals. This will, of course, burden the hospital's operational costs. The solution to reducing groundwater use is the use of microfiltration membranes. Microfiltration membranes can be used to recycle wastewater into clean water so that it can be collected and used for cleaning, washing, and watering gardens. They can reduce groundwater taxes and hospital groundwater use. The research objectives are to know the efficiency of reducing wastewater recycling equipment from the wastewater treatment plant (WWTP) outlet using a microfiltration membrane. The research methodology used was a quasi-experiment in laboratories and workshops, with a pre-test (before treatment) and post-test (after treatment) design. Stage one Microfiltration Membrane is a medium for processing wastewater into clean water in the first stage. Stage two, Microfiltration Membrane, is a medium for processing wastewater into clean water. In the second stage, it ensures that clean water quality is met. The results that the efficiency of reducing the wastewater recycling equipment from the WWTP outlet usingÂ Microfiltration Membrane for pH 7%, Temperature 6%, Turbidity 64%, Colour 85%, Dissolved Solids (TDS) 40%, Nitrate 70%, Nitrite 94%, dissolved Iron (Fe) 33%, ManganeseÂ 60%, Cadmium 50%, LeadÂ 43%, Fluoride 46%, Cyanide 96%, Hardness (CaCO3) 11%. In conclusion, all the parameters studied experienced a decrease in concentration. This research suggests conducting further research to reduce the current research discharge so that the parameter reduction can be more significant.